Baseline structural imaging correlates of treatment outcomes in semantic variant primary progressive aphasia. (January 2023) - Dial, Heather R.; Europa, Eduardo; Grasso, Stephanie M.; Mandelli, Maria Luisa; Schaffer, Kristin M.; Hubbard, H. Isabel; Wauters, Lisa D.; Wineholt, Lindsey; Wilson, Stephen M.; Gorno-Tempini, Maria Luisa; Henry, Maya L.
Abstract: Semantic variant primary progressive aphasia (svPPA) is a neurodegenerative disorder characterized by a loss of semantic knowledge in the context of anterior temporal lobe atrophy (left > right). Core features of svPPA include anomia and single-word comprehension impairment. Despite growing evidence supporting treatment for anomia in svPPA, there is a paucity of research investigating neural mechanisms supporting treatment-induced gains and generalization to untrained items. In the current study, we examined the relation between the structural integrity of brain parenchyma (tissue inclusive of gray and white matter) at pre-treatment and treatment outcomes for trained and untrained items in a group of 19 individuals with svPPA who completed lexical retrieval treatment. Two structural neuroimaging approaches were used: an exploratory, whole-brain, voxel-wise approach and an a priori region of interest (ROI) approach. Based on previous research, bilateral temporal (inferior, middle, and superior temporal gyri), parietal (supramarginal and angular gyri), frontal (inferior and middle frontal gyri) and medial temporal (hippocampus and parahippocampal gyri) ROIs were selected from the Automated Anatomical Labeling (AAL) atlas. Analyses revealed improved naming of trained items and generalization to untrained items following treatment, providing converging evidence that individuals with svPPA can benefit from treatment for anomia. Better post-treatment naming accuracy was associated with the structural integrity of inferior parietal cortex and the hippocampus. Specifically, improved naming of trained items was related to the left supramarginal (phonological processing) and angular gyri (phonological and semantic processing), and improved naming of trained and untrained items was related to the left hippocampus (episodic, context-based memory). Future research should examine treatment outcomes in relation to pre-treatment functional and structural connectivity as well as changes in network dynamics following speech-language intervention to further elucidate the neural mechanisms underlying treatment response in svPPA and related disorders.